Therapeutic Effects of Low-Level Laser Therapy on Rat Spinal Cord Injury: Analysis of Inflammatory Markers and Testicular Function: Therapeutic effects of low-level laser therapy on rat spinal cord injury - Taheri, Hadise; Mosleh, Hamid Reza; Jahanbaz, Shima; Aliaghaei, Abbas; Tahmasebinia, Foozhan; Abedi, Marzieh; Abbasi, Sama; Abbaszadeh, Hojjat-allah (Journal of Lasers in Medical Sciences, 2025)
Introduction: Spinal cord injury (SCI) is a severe condition often leading to lasting neurological impairment and associated reproductive health issues in males. The aim of this study was to investigate the therapeutic potential of photobiomodulation therapy (PBMT) during the inflammatory phase of SCI to prevent oxidative damage, reduce inflammation, and mitigate potential damage to testicular function. Methods: Eighteen male rats were randomly divided into three groups: Group A (laminectomy only), group B (contusion), and group C (contusion + PBMT). Thirty minutes post-injury, group C received PBMT for two weeks. Histological and stereological analysis was evaluated using the hematoxylin and eosin test (H&E). ELISA and real-time PCR were performed for eight weeks post-SCI to assess testosterone and inflammatory and apoptotic changes. Statistical analysis was performed using SPSS with one-way ANOVA and Tukey’s post hoc test, and statistical significance was set at P < 0.05. Results: The SCI group exhibited significant reductions in sperm count (mean ± SD: 14.2 ± 86.1), motility (34.8 ± 72.8), and viability (26.12 ± 43.9), with increased levels of inflammatory markers (IL-1 β: 4.4 ± 71.6, TNF-α: 3.14 ± 66) and damage to testicular structure. In contrast, animals treated with PBMT showed significant improvements in sperm parameters (sperm count: 48 ± 34, motility: 57.2 ± 18.5, viability: 52 .3 ± 88.2) and a marked reduction in inflammation (IL-1 β: 3.09 ± 14.2, TNF-α: 2.67 ± 74.1) compared to untreated SCI animals (P < 0.001). Additionally,PBMT-treated animals demonstrated significant improvements in testosterone levels (1.57 ± 44.8) and a reversal of testicular cell loss (P < 0.001). Conclusion: These findings suggest that PBMT mitigates the negative effects of SCI on testicular tissue by reducing inflammation and preserving cellular integrity, thus supporting its use as a dual therapeutic approach to aid neurological recovery and maintain reproductive health.